Structure and mechanism of anthocyanidin synthase from Arabidopsis thaliana. - Wilmouth, R; Turnbull, J; Welford, R; Clifton, I; Prescott, A; Schofield, C (2002)
Flavonoids are common colorants in plants and have long-established biomedicinal properties. Anthocyanidin synthase (ANS), a 2-oxoglutarate iron-dependent oxygenase, catalyzes the penultimate step in the biosynthesis of the anthocyanin class of flavonoids. The crystal structure of ANS reveals a multicomponent active site containing metal, cosubstrate, and two molecules of a substrate analog (dihydroquercetin). An additional structure obtained after 30 min exposure to dioxygen is consistent with the oxidation of the dihydroquercetin to quercetin and the concomitant decarboxylation of 2-oxoglutarate to succinate. Together with in vitro studies, the crystal structures suggest a mechanism for ANS-catalyzed anthocyanidin formation from the natural leucoanthocyanidin substrates involving stereoselective C-3 hydroxylation. The structure of ANS provides a template for the ubiquitous family of plant nonhaem oxygenases for future engineering and inhibition studies.